2021
DOI: 10.1016/j.jamcollsurg.2020.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interdisciplinary Approach to GERD: Concomitant Laparoscopic Hiatal Hernia Repair with Transoral Incisionless Fundoplication

Abstract: BACKGROUND: Transoral incisionless fundoplication (TIF) is an endoscopic alternative for the treatment of GERD. However, TIF does not address the hiatal hernia (HH). We present a novel approach with a laparoscopic HH repair followed by same-session TIF, coined concomitant transoral incisionless fundoplication (cTIF). The aim of this study was to assess the efficacy, safety, and feasibility of cTIF in a collaborative approach between Gastroenterology and surgery. ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Patients who underwent obligatory dissection and hiatal repair, regardless of the presence of a hiatal hernia, fared better by multiple measures compared to patients without obvious hernia who had MSA placed using minimal dissection without cruroplasty [Table 1] [18,19] . These MSA studies and two small studies of transoral incisionless fundoplication (TIF) combined with a laparoscopic hiatal hernia repair [20,21] provide clinical confirmation that failure or inability to restore the crural sphincter may be an inherent limitation of endoscopic therapies, regardless of the presence or absence of a hiatal hernia.…”
Section: The Diaphragmatic Sphincter and Transoral Therapiesmentioning
confidence: 99%
“…Patients who underwent obligatory dissection and hiatal repair, regardless of the presence of a hiatal hernia, fared better by multiple measures compared to patients without obvious hernia who had MSA placed using minimal dissection without cruroplasty [Table 1] [18,19] . These MSA studies and two small studies of transoral incisionless fundoplication (TIF) combined with a laparoscopic hiatal hernia repair [20,21] provide clinical confirmation that failure or inability to restore the crural sphincter may be an inherent limitation of endoscopic therapies, regardless of the presence or absence of a hiatal hernia.…”
Section: The Diaphragmatic Sphincter and Transoral Therapiesmentioning
confidence: 99%
“…A mucosal tear occurred in one patient intraoperatively. On postoperative day 1, one patient suffered a non-life-threatening upper gastrointestinal hemorrhage and ileus, and another was readmitted for gas bloat and delayed stomach emptying [48]. At six months of follow-up, another retrospective review analysis revealed statistically significant improvements in GERD-HRQL and RSI scores in 29 patients and normalization of EAE after c-TIF in 21 out of 22 patients.…”
Section: C) Concomitant Transoral Incisionless Fundoplication (C-tif)mentioning
confidence: 99%
“…The c-TIF (also known as HH-TIF: combined laparoscopic hiatal hernia repair with TIF 2.0) is a new modified approach that combines laparoscopic hiatal hernia repair and TIF in the same session. Choi et al [48] enrolled 60 patients in their c-TIF trial, with an average age of 59.3 years and a BMI of 30.0 kg/m 2 . This study comprised people with BE, LA grade C/D esophagitis, a mean HH of 2.9 ± 1.5 cm, and HG I-IV.…”
Section: C) Concomitant Transoral Incisionless Fundoplication (C-tif)mentioning
confidence: 99%
“…There continues to be an increased interest in performing TIF along with concomitant laparoscopic hiatal hernia repair (cTIF) [47]. For surgeons performing both LARS and TIF, the rationale for cTIF includes: (1) a trend away from Nissen Fundoplication due to higher incidence of postoperative gas/ bloat and dysphagia coupled with established data that TIF produces much less gas/bloat, dysphagia [2], and emerging data suggesting that cTIF also produces less gas/bloat than traditional LARS [34,35,48], (2) the non-standardization of the partial fundoplication (Dor or Toupet), and (3) the concern over potential effects of stronger MRI machines in the future on the magnetic sphincter augmentation device [49].…”
Section: Concomitant Laparoscopic Hernia Repair and Tifmentioning
confidence: 99%